Increasing The Business Performance Over Human Capital Contribution On Creative Industry In Banyumas Regency - Alisa Tri Nawarini; Ekaningtyas Widiastuti; Sulistyandari Sulistyandari; Suci Indriati (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2018)
This study aims to determine the effect of human capital (innovation and creation, education and learning and experience and expertise) on business performance of actors in the creative industry sector in Banyumas regency. This research is a quantitative research by using survey method. The data collection was done by distributing questionnaires to 50 SMEs perpetrators of creative industry sector in Banyumas Regency. The method of analysis used to test the research hypothesis is multiple linear regression method. There are findings that the employees of the creative industry business have mostly had a long working period and have expertise in the field of work. They can show their best performance consistently in carrying out their work and being professional. It can be said that human capital in the form of experience and expertise has a role in influencing and improving company performance. Increased human capital owned by creative business actors can be done by involving employees in trainings (either training held by the government or private parties). By involving employees in the training, it is expected to improve the insights, skills and capabilities of individual employees so that ultimately able to improve performance in an effort to develop its business.